Critical Skills, Mathematics, and Disinformation: a Necessary Dialogue for the Formation of the 21st-Century Citizen - Ledur, José Ricardo; dos Santos, Renato Pires (Seven Editora, 2023)
Education, in particular, has the task of equipping young people to become contributing members of a democratic society. Specifically, mathematics and science education has been the central place where students learn the skills to discern facts, process information and draw conclusions, and practice ways of seeking true knowledge. This art of thinking is considered vital for democratic societies to thrive. In the contemporary world, the information society requires from its citizen's skills that provide the ability to access, interpret and evaluate the information that is made available at an increasingly fast pace. Literacies, especially in the fields of science, mathematics, and media, are increasingly becoming essential elements for the country's autonomy, quality of life, and development. This work aims to highlight converging points between mathematical literacy in the context of post-truth and the growing proliferation of misinformation, seeking to provide greater clarity about these concepts as well as emphasizing the importance of this skill for a full education of our students. Analyzes of information conveyed through the media are presented, emphasizing the need for the capacity for analysis and mathematical interpretation for the critical evaluation of news. We consider that, in general, in Brazilian education, in practice, these concepts are still treated in an incipient way. And since the relationship between literacy and knowledge is complex, as both are concepts in transformation, their discussion seems to be increasingly necessary. DOI: https://doi.org/10.56238/methofocusinterv1-033